Analysis of Prefixes in the Novel "Belahan Jiwa" By Nuniek Kr: Exploration of the Purpose and Impact of Writing - Zendrato, Solina; Bawamenewi, Arozatulo; Giawa, Yarniwati; Zendrato, Krisna Ifariani (Journal of Computer Science Advancements, 2024)
The aim of this research is to analyze the prefixes contained in the novel "Belahan Jiwa" by Nuniek KR. This research uses a qualitative method with a descriptive approach. Several instruments that can be used in this research are text selection, text annotation, morphological classification, context analysis, meaning interpretation, analysis notes and validation. The technique used in this research is the reading and note taking technique. The steps used in this technique include reading, analyzing and understanding the structure, marking certain parts according to analysis needs, recording data in the form of sentences and words related to the word formation process, grouping data or classifying data based on the word formation process and analyzing and concluding data based on the results of reading and recording the word formation process in the novel "Belahan Jiwa" by Nuniek KR. Based on the results of the analysis carried out, there are 8 (eight) uses of prefixes, namely the prefixes ber-, me-, mem-, per-, se-, di-, ke-, and ter-. In the novel "Belahan Jiwa" by Nuniek KR, it can be seen that there are 51 words that use the prefix ber-, for the prefixes me- 59, mem- 19, per-11, se-24, di-13, 14th and ter-25th.